2021
DOI: 10.1186/s12872-021-02242-9
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial appendage orifice area and morphology is closely associated with flow velocity in patients with nonvalvular atrial fibrillation

Abstract: Background Thromboembolic events are the most serious complication of atrial fibrillation (AF), and the left atrial appendage (LAA) is the most important site of thrombosis in patients with AF. During the period of COVID-19, a non-invasive left atrial appendage detection method is particularly important in order to reduce the exposure of the virus. This study used CT three-dimensional reconstruction methods to explore the relationship between LAA morphology, LAA orifice area and its mechanical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 37 publications
0
8
0
5
Order By: Relevance
“…The minor axis of the LAA orifice in the AF group was longer than that of the control group, but the major axis of the two groups was similar. As a result, the shape of the LAA orifice changed from oval to circular in AF patients, which might affect the hemodynamics and accelerate thrombus formation of the LAA ( 18 , 19 ), even though it was not an independent risk factor of AF as compared with LAA volume and LA volume.…”
Section: Discussionmentioning
confidence: 99%
“…The minor axis of the LAA orifice in the AF group was longer than that of the control group, but the major axis of the two groups was similar. As a result, the shape of the LAA orifice changed from oval to circular in AF patients, which might affect the hemodynamics and accelerate thrombus formation of the LAA ( 18 , 19 ), even though it was not an independent risk factor of AF as compared with LAA volume and LA volume.…”
Section: Discussionmentioning
confidence: 99%
“…In a multi-linear regression analysis, LAA morphology was found to be the significant determinant of LAA flow velocity ( 99 ). In other studies, flow velocity was shown to be negatively correlated with orifice size, and many studies found that a greater orifice size usually resulted in decreased flow velocity ( 32 , 47 , 53 ). CFD was also applied in studies relevant to morphology parameters in which LAA length, orifice area, tortuosity, etc.…”
Section: Discussionmentioning
confidence: 93%
“…This seems more accurate and less subjective compared to the intuitive definition, and is used as the measurement method for LAA orifice in ( 52 ). However, several studies have defined the LAA orifice as the narrowest portion at the entrance into the left atrium ( 49 , 53 ). We deduced that this wide-spread definition had its origins in studies of LAA occlusion, as the location of occlusion is usually defined as the narrowest portion ( Figure 3 , orange dashed line), which would be defined as the LAA neck in our context.…”
Section: Laa Characteristics Related With Strokementioning
confidence: 99%
See 1 more Smart Citation
“…constructed a model for predicting LAAT based on three independent risk factors: left atrial appendage emptying velocity (LAAEV), LA or LAASEC, and less than moderate to severe mitral regurgitation [AUC = 0.88, 95% CI: 0.82–0.95]. LAAEV [ 22 , 23 ] and LAA morphology [ 24 ] are often considered risk factors for LAAT, but considering that they are mainly measured by TEE, they are not included in multivariate analysis. Due to the different medical levels of center levels, we tried to choose simple and easily available indicators for further research.…”
Section: Discussionmentioning
confidence: 99%